Advances in the systemic administration of nanotechnology-mediated drug delivery systems in melanoma treatment: a systematic review - Mohammad Fereidouni; Yasamin Roointanpour; Hossein Movahed; Ali Taghipour; Armaghan Vafafar; Mirza Ali Mofazzal Jahromi (Discover Applied Sciences)
Abstract Melanoma is the deadliest type of skin cancer due to its high death rate resulting from active metastasis. Risk factors for its development include exposure to ultraviolet radiation and facial and eye clarity. There are limitations to conventional therapies for melanoma. A promising avenue is nanotechnology-based therapies, which deliver therapeutic agents precisely and target them while minimizing side effects. In this systematic review, we carried out a literature review of articles that investigated the systemic administration of nanotechnology-based drug delivery in melanoma models. Articles from January 1990 to March 2024 were analyzed from the Web of Science, PubMed/Medline, and Scopus databases. We searched for articles containing “Nano*” and “Melanoma” and analyzed them according to our inclusion and exclusion criteria. A total of 1914 studies were screened on the basis of the inclusion criteria, and 19 studies were eligible for this review. The results obtained indicated that systemic administration of nanotechnology-based drugs reduced melanoma tumor size and systemic side effects both in vivo and in vitro. Nanotechnology-based drug delivery systems can potentially target melanoma tumor cells and reduce tumor growth via systemic administration. Thus, these nanosystems have the potential to be effective systemic melanoma treatments and require further investigation for use in human models.